2018
DOI: 10.1016/j.nicl.2017.12.013
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic functional connectivity in Parkinson's disease patients with mild cognitive impairment and normal cognition

Abstract: The objective was to assess dynamic functional connectivity (FC) and local/global connectivity in Parkinson's disease (PD) patients with mild cognitive impairment (PD-MCI) and with normal cognition (PD-NC).The sample included 35 PD patients and 26 healthy controls (HC). Cognitive assessment followed an extensive neuropsychological battery. For resting-state functional MRI (rs-fMRI) analysis, independent component analysis (ICA) was performed and components were located in 7 networks: Subcortical (SC), Auditory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
156
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 155 publications
(163 citation statements)
references
References 57 publications
7
156
0
Order By: Relevance
“…In a recent study investigating the dynamic component of functional connectivity, it was found that subjects with PD and MCI showed reduced dwell time in a hypoconnectivity state and had increased number of state transitions. Meanwhile, there was reduced internetwork connectivity in the hypoconnected state . It should be noted that there are significant limitations to the sliding window method used in the aforementioned study, such that these results must be interpreted carefully .…”
Section: Discussionmentioning
confidence: 90%
“…In a recent study investigating the dynamic component of functional connectivity, it was found that subjects with PD and MCI showed reduced dwell time in a hypoconnectivity state and had increased number of state transitions. Meanwhile, there was reduced internetwork connectivity in the hypoconnected state . It should be noted that there are significant limitations to the sliding window method used in the aforementioned study, such that these results must be interpreted carefully .…”
Section: Discussionmentioning
confidence: 90%
“…PD patients that did not fulfill these specific criteria were classified as PD with normal cognition (PD‐NC). The details of the PD‐MCI classification have been extensively described in a previous study . According to this criteria, we have investigated the MCI in our sample.…”
Section: Methodsmentioning
confidence: 99%
“…Meanwhile, a series of dFC studies (Patanaik et al, 2018;Wang et al, 2016;Yeo et al, 2015) assessed two discrete connectivity states representing brain activities of high and low arousal levels of which the latter one was accompanied by an impairment of cognitive performance especially with respect to PVT-lapses, speed of PVT processing and 3-back working memory. Additionally, during an auditory vigilance task (AVT)-based fMRI scanning, the AVT-lapses were significantly positively and negatively correlated with low arousal and high arousal states, respectively (Diez-Cirarda et al, 2018;Marusak et al, 2017;Rashid et al, 2018). Allen et al (2014) attributed this state to the average of large numbers of extra connectivity states that were not adequately distinct or frequent to be separated.…”
Section: Discussionmentioning
confidence: 99%
“…Next, the dFC properties were used for investigating their timevarying abnormalities in specific populations compared to healthy controls Diez-Cirarda et al, 2018;Dong et al, 2018;Rashid et al, 2018). For example, Rashid et al (2018) observed that a high level of autistic traits and autism spectrum disorder diagnosis was closely associated with a globally disconnected FC pattern in 774 6-to 10-year old children.…”
mentioning
confidence: 99%